ANALYSIS IMPLEMENTATION OF A 360 DEGREE FEEDBACK PERFORMANCE APPRAISAL SYSTEM TO SUPPORT INNOVATIVE WORK BEHAVIOR, PERFORMANCE APPRAISAL FAIRNESS, COMMITMENT AND INDIVIDUAL PERFORMANCE FOR CIVIL SERVANTS - Toman Sony Tambunan; Paham Ginting; Sirojuzilam Sirojuzilam; Yeni Absah (Green Publisher, 2022)
The literature on 360-degree feedback performance appraisal systems has attracted considerable attention by showing a link between behavior change and individual performance. This study aims to analyze the strengths, weaknesses, opportunities and threats to the 360-degree feedback performance appraisal system for Civil Servants in the City Government of Medan. Data collected through observations, interviews and literature studies. Data analysis uses qualitative descriptive analysis. The data results will be used to determine the strengths, weaknesses, opportunities and threats to the implementation of the Civil Servants' 360-degree feedback performance assessment system in the City Government of Medan.